Pengembangan Model Pembelajaran Digital Storytelling untuk Meningkatkan Literasi Keberlanjutan dan Keterampilan Berpikir Kritis Mahasiswa - Noor Hujjatusnaini; Mila Mila (Simpati, 2026)
Strengthening sustainability literacy and critical thinking skills has become an essential priority in higher education to prepare students for the global challenges of the 21st century. One promising instructional approach to address this need is Digital storytelling. This study aimed to develop a Digital storytelling learning model that is valid, practical, and effective in enhancing students' sustainability literacy and critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE framework, consisting of the analysis, design, development, implementation, and evaluation stages. The participants included 40 undergraduate students from the Biology Education Program at the State Islamic University of Palangkaraya, as well as subject matter experts and instructional experts. Data were collected through expert validation sheets, critical thinking and sustainability literacy tests, practicality and student perception questionnaires, and semi-structured interviews. Data were analyzed using descriptive statistics, N-Gain calculations, and thematic analysis. The findings indicated that the developed Digital storytelling learning model demonstrated high levels of validity and practicality. The effectiveness test revealed moderate to high improvements in students' critical thinking skills and sustainability literacy based on pretest and posttest scores. Qualitative findings further confirmed that Digital storytelling fostered meaningful, contextual, and reflective learning experiences through the integration of sustainability issues into digital narratives. It can be concluded that the developed Digital storytelling learning model is feasible as an innovative instructional alternative to support the development of 21st-century competencies in higher education.